Pengaruh Latihan Teknik Dasar Bermain Sepak Bola terhadap Kekuatan Otot Tungkai dan Kadar Mioglobin Darah pada Pemain Sepakbola Sekolah Sosial Olahraga (SSO) Real Madrid Foundation Aceh - Yuni Rahmayanti; Saifuddin Saifuddin; Yasmeini Yazir (Majalah Kedokteran Indonesia, 2018)
Introduction : The practice of basic technique of soccer is one of method in order to increase the strength of leg muscle. The strength of leg muscle is very important to support the achievement of soccer player, but not with cut any side effect. One of the side effects is the damage of muscle that influences the achievement. Myoglobin (Mb) is celluler protein that bind O2 in the muscle cell and heart and for human has function as biomarker of the damage muscle. Mb in a certain condition found in the blood and can found by the assessment of myoglobin serum. The aim of the study is to observe the influence of basic technique practice of soccer to the strength of leg muscle and content of blood myoglobin to the soccer player in the sport social school (SSO) Real Madrid Foundation Aceh. Method : 30 soccer players of sport social school (SSO) Real Madrid Foundation Aceh whose age 10-13 years old involved in the basic technique practice of soccer during 4 weeks in the frequency of 4 times in a week. Four hour before practice inthe first day, all of subject are measured such as the demography data (age, body weight and height of body) and the strength of leg muscle and blood (pre test). After 16 time practice, in the last 4 hours the same subject are measured (post test). Results : The basic technique practice of soccer has a signif icant influence to the increasing of strength of leg muscle (p=0.000), but the basic technique practice of soccer has not significant influence to the increasing of blood myoglobin (p=0.666). Conclusion : The basic technique practice of soccer is effective to increase the strength of leg muscle but did not cause the significant muscle damage.